DIVERSITY AND ECOLOGY OF LAND SNAILS IN GUNUNG HALIMUN SALAK NATIONAL PARK (GHSNP) IN JAVA, INDONESIA - Ayu Savitri Nurinsiyah; Ita Faizah; Yogi Prasetio; Tedi Setiadi; Ristiyanti Marsetiowati Marwoto; Bernhard Hausdorf (ZOO INDONESIA, 2019)
The land snail fauna of the largest tropical montane forest in Java, the Gunung Halimun Salak National Park (GHSNP), was surveyed during the dry season (June-July) in 2015, concentrating on four park’s resorts, i.e. Cikaniki, Mt. Botol, Cisarua (Halimun area) and Cidahu (Salak area). In total, 399 specimens representing 43 species were collected. Prior to the surveys, 48 land snail species were known from the GHSNP. Fifteen new records for the GHSNP were discovered so 63 species are now known to inhabit the Park. This number represent 25% of the total land snail fauna of Java. 21 of the species found in GHSNP are endemic to Java. The species richness of the plots in GHSNP was correlated with soil pH and the composition of the land snail communities was correlated with elevation, annual mean temperature, and amount of deadwood.